A rapid albumin-binding 5-fluorouracil prodrug with a prolonged circulation time and enhanced antitumor activity. (24th January 2017) - Zhao, Dongyang; Zhang, Huicong; Tao, Wenhui; Wei, Wei; Sun, Jin; He, Zhonggui
Abstract : A rapid albumin-binding 5-FU prodrug has been designed and evaluated. It could form a drug–albumin conjugate nanomedicine for favorable drug delivery after intravenous administration. Abstract : 5-Fluorouracil (5-FU) is an antimetabolite widely used in the treatment of a variety of solid tumors. However, its clinical applications are greatly hindered by a very short residence time in blood circulation and non-specific distribution in the body. In order to overcome these challenges, 1-alkylcarbonyloxymethyl 5-FU was designed and linked with a maleimide group to form an albumin-binding 5-FU prodrug, namedEMC-5-FU . In vitro incubation with bovine serum albumin (BSA) and fresh rat blood proved that the prodrug bound rapidly to cysteine-34 to form the drug–albumin conjugate nanomedicine. The conjugate BSA–EMC-5-FU was stable under acidic and neutral conditions but an unstable compound to release 5-FU in alkaline solution, and such a property was used for the determination of total 5-FU concentration in plasma. The t 1/2 and AUC values of total 5-FU after an intravenous injection ofEMC-5-FU to SD rats were significantly increased, about 43-fold and 93-fold higher than those of 5-FU following 5-FU intravenous administration, respectively. In vivo fluorescence images ofEMC -Cy5 indirectly demonstrated the selective tumor accumulation ofEMC-5-FU . In H22 tumor-bearing mice models, treatment withEMC-5-FU was more efficacious in tumor inhibition compared to 5-FU intravenous administration. In conclusion, a rapid albumin-binding prodrug strategy addresses concerns related to the poor circulation half-life and non-specific distribution of anticancer drugs, and paves the way for the development of in vivo -forming nanomedicines in clinical cancer therapy.